Depositional Modification In Seram Through, Eastern Indonesia - Dida Kusnida; Tommy Naibaho; Yulinar Firdaus (Pusat Survei Geologi, 2016)
Seismic reflection profiles considered to represent the morphotectonics of the study area and verified by surficial sedimentary data presented in this paper directed to understand Â the sedimentary depositional dynamics. Â Seismic data interpretation results show the gradation and sediment facies cycles in accordance with the episode of tectonic activities, which is characterized by the avalanche of the Seram Trough base-of slopes materials. Seismic data reveal more than 1250 meters acoustically chaotic to laminated, indicate fine-grained sediments between slumps at its base of slope and fine marine sediments at the trough floor. Thus, it suggests that the Seram Trough is in the process of differential vertical movement causing depositional modification due to the accretionary prism growths.